Genetic Diversity of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) From 1996 to 2017 in China - Jiang, Yifeng; Li, Guoxin; Yu, Lingxue; Li, Liwei; Zhang, Yujiao; Zhou, Yanjun; Tong, Wu; Liu, Changlong; Gao, Fei; Tong, Guangzhi (Frontiers in Microbiology, 2020)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most devastating diseases of the global swine industry. The causative agent porcine reproductive and respiratory syndrome virus (PRRSV) was first isolated in China in 1996 and has evolved quickly during the last two decades. To fully understand virus diversity, epidemic situation in the field, and make future predictions, a total of 365 PRRSV strains were used for evolution and genome analysis in which 353 strains were isolated from mainland China. The results showed that high diversity was found among PRRSV isolates. Total PRRSV isolates could be divided into eight subgroups. Among these subgroups strains, Original HP-PRRSV, NADC30-like, and Intermediate PRRSV were the major epidemic PRRSV strains circling in the field and would play a major role in PRRS epidemic in the future. Deletions, insertions, and recombinations have occurred frequently in the PRRSV genome. Deletions were the main driving force of viral evolution before 2006 and may also contribute further to the virus' evolution in a relatively closed or low strain diversity circumstance. The recombinant strains could be divided into three groups: the Inner group, Extensional group, and Propagating group. The evolutionary directions of the isolates in the Extensional and Propagating groups have changed, and the routes of recombination in the Propagating group were analyzed and sorted into three types. The increases in recombinant strains and high rates of recombination in recent years indicate that recombination has played a very important role in the virus' evolution. Isolates, which incorporate the advantages of their parental strains, will influence PRRSV evolution and make adverse effects on PRRS control in the future.